Correlation between Age and Surgical Approach for Thoracic and Lumbar Hemivertebra - Nikova, Alexandrina; Chatzipaulou, Varvara; Malkots, Belkis; Mustafa, Reichan Molla; Valsamidou, Christina; Birbilis, Theodosis (Indian Journal of Neurosurgery, 2020)
Objective Hemivertebra (HV) is a congenital defect of the formation of the spinal vertebra, which can result in scoliosis or kyphosis along with the related symptomatology of spine deformity. More often than not, it is linked to other abnormalities and requires attention. Its management is surgical and it is of great importance for the physician to choose the right approach at the right time, due to its deteriorative prognosis.Methods Due to the interest of the subject, the authors investigated the world literature between 1990 and 2018 and found 45 articles, reporting thoracic, thoracolumbar, and lumbar HV in children and its postsurgical outcome, aiming to show whether the approaches are equal in terms of the final outcome.Results The chosen surgical method depends much on the level of the pathology. Despite this fact, after analyzing the included data, we found that the surgical techniques are unequal with regard to the purpose of achieving improvement. Age, caudal and cranial curves, segmental kyphosis, and scoliosis are factors playing a major role in this.Conclusion If not treated, HV leads to deterioration and dysfunction. The most optimal result, however, is achieved only when the surgical approach is applied according to age and rest of the accompanying factors, which should be considered in future management planning.
Keywords: hemivertebra; quality of life; spine surgery